PENGUKURAN KUALITAS LAYANAN WEBSITE PERGURUAN TINGGI DENGAN MENGGUNAKAN METODE WEBQUAL - Sauda, Siti ; Sopiah, Nyimas (JURNAL ILMIAH MATRIK, 2015)
College website is an online-based applications that used several universities to connected with the external and internal. Facility that can be used on this website include announcements, academic systems, and media promotion. Service a website can be measured to determine the level of satisfaction of the end user and the feedback. In this study, the quality of the website can be measured using the method WebQual. WebQual is one method or technique of measuring the quality of a website is based on the perception of the end user. The variables of webqual is usability, information quality and service interactions are independent variables, wether the dependent variable is user satisfaction. The analysis used is multiple linear regression analysis. This study resulted in a significant influence of three independent variables on the dependent variable, where the highest order is the interaction of services, the quality and usefulness of the information.